The design and testing of dielectric-loaded linear electron accelerator structures - Moffat, M (1964)
The usefulness of a linear electron accelerator in providing short bunches of relativistic electrons for injection into interwave sources such as magnetic undulators and Cerenkov couplers is pointed out. Shorter bunch lengths can result in coherent radiation at shorter wavelengths. An experimental example of this effect is given, and the design of a linac to produce short electron bunches is then described. The historical background to the choice of a dielectric disc-loaded slow-wave structure is explained together with the reasons for adopting a 2 MeV beam energy and a 1.8 cm operating wavelength. Periodically loaded waveguides and their mode of operation as linac slow-wave structures are described, and the reasons for favouring travelling-wave operation with a phase change per periodic length of π/3 radians are given. Phase space concepts applied to the design of the electron buncher and main accelerator section are shown to give an accurate description of the fields and wave velocities required for good bunching and small bean energy spread. The theoretical design to give an effective bunch length of 0.3 mm is described. Measurements and proving tests at high and low R.F. power, and the investigation of physical and chemical properties relating to linac fabrication and operation indicate that certain titania and magnesium titanate ceramics are suitable as loading material, provided that some precautions are taken against surface breakdown, this appears to be initiated by sparking between the dielectric-loading disc rims and the metallic wall of the linac structure. The sparking can be greatly- reduced by grinding the rims to a fine finish and metallizing them with copper. Surface breakdown can be inhibited by coating the discs with a thin protective layer of lead borate glaze or P.T.F.F. Electron multipactor resonances between discs are largely avoided by excluding oil from the evacuated system. The dielectric surface conductivity is very low and so a well focused electron beam is essential if surface charging is to be avoided. Theoretical and experimental results for the test structures are not in close agreement, especially for shunt impedance. Ohmic losses are about four times higher than the theory suggests. This is thought to be due partly to inexact boundary-matching of fields in the theory, and partly to surface effects giving rise to a relatively high resistivity in the waveguide wall. Practical test cavities give consistent and repeatable results, and the necessary high degree of physical accuracy has been attained in their construction. A practical design and fabrication method is given for the main accelerator section, and the proposed physical realisation of the buncher-accelerator system is described.